Comparative Study of the Political Economy Power of Russia and Ukraine - Feny Avisha; Guntur Eko Saputro; Lukman Yudho Prakoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
Protracted Russia - Ukraine conflict that occurred from the beginning of February 2022 caused the world economy to falter. This condition is one of the reasons for the projection that the world economy will experience a recession. These conditions made the world shake given their dependence on Ukraine, especially on the wheat sector. Wheat farmers in Ukraine have difficulty harvesting wheat. This condition makes Russia and Ukraine have to survive, and one of the factors is the economic factor. The comparison of the strengths of these countries needs to be reviewed considering that these two countries are world players in each of the sectors that affect their defense. This paper uses the theory of national power which is narrowed down to aspects of geography, natural resources, human productivity, and industrial capabilities. This paper uses a qualitative method with a comparative study approach. The results and discussion of this paper provide an overview of the capabilities in each aspect. This paper concludes that Russia is superior in political economy to Ukraine